Diurnal cycle of raindrops size distribution in a valley of the peruvian central Andes - Villalobos-Puma, E. (2020)
In the Central Andes of Peru, convective and stratiform rainfall occurs, frequently associated with convective storms. The raindrop size distributions (RSD), measured by a Parsivel-2 optical disdrometer, were characterized by the variation of their normalized parameters. The RSD dataset includes measurements corresponding to 18 months between 2017 and 2019. As a result, it was found that the mass-weighted mean diameter Dm and the Nw parameter present respectively high and low values, in the interval of 15-20 LST (local standard time), wherein deeper and more active clouds appear. The events including convective rainfall contribute 67.5% of the accumulated total, wherein 92% corresponds to the 15-20 LST interval. It is concluded that the spectral variability of the RSD is strongly controlled by the cloudiness configuration field developing over the west (convection over highlands) and east (convection over Amazon) sides of the valley. In the afternoon, clouds develop and drift to the east, over the Andean valleys and towards the Amazon, intensified by local orographic circulation. The opposite happens at night, when the stratiform rainfall is dominant and it is controlled by clouds, located in the Inter-Andean valley, generated by the convection fields formed over the Amazon forest. © 2019 by the authors.